Tumor Necrosis Factor Gene Polymorphisms, Leukocyte Function, and Sepsis Susceptibility in Blunt Trauma Patients - Majetschak, Matthias (American Society for Microbiology, 2002)
The tumor necrosis factor alpha (TNF-α) −308 G/A and TNF-β NcO1 polymorphisms have been described to be associated with an increased risk for sepsis in critically ill patients. Functional consequences associated with these polymorphisms remain unclear. We compared the genotype distribution of these TNF polymorphisms with susceptibility to severe sepsis and leukocyte function in blunt trauma patients (n = 70; mean injury severity score, 24 points [range, 4 to 57). Severe sepsis was defined according to the American College of Chest Physicians-Society of Critical Care Medicine consensus conference criteria. Genotyping for the NcO1 polymorphism (alleles TNFB1 and TNFB2) was performed by PCR and digestion of the products with NcO1, and that for the TNF-α −308 G/A polymorphism (alleles TNF1 and TNF2) was performed by real-time PCR. Leukocyte function was assessed by measurement of the production of endotoxin-induced cytokines (TNF-α, interleukin-6 [IL-6], and IL-8) in whole blood. TNF-α, IL-6, and IL-8 were determined by enzyme-linked immunosorbent assay. For the genotypes of the TNF-α −308 G/A polymorphism, differences in the frequency of development of severe sepsis were not detectable. Patients developing severe sepsis after trauma were significantly more likely to posses a homozygous genotype of the TNF-β NcO1 polymorphism. Compared with heterozygotes, the odds ratio for the TNFB2/B2 genotype for the development of severe posttraumatic sepsis was 11 (P = 0.01), and that for the TNFB1/B1 genotype was 13 (P = 0.014). TNF-α −308:TNF-β NcO1 haplotype analysis showed that the TNFB2:TNF2 haplotype is significantly negatively associated with development of severe sepsis. Patients homozygous for the TNFB1 or TNFB2 allele showed a persistently higher cytokine-producing capacity during at least 4 to 8 days after trauma than the heterozygotes. In patients homozygous for the TNF1 allele, a higher TNF-α- and IL-8-producing capacity was found only at day 1 after trauma. Although the TNF-β NcO1 polymorphism appears to be less likely to be causative for development of severe sepsis after trauma, it is thus far the only genetic marker identified which can be used as a relevant risk estimate for severe sepsis in trauma patients immediately after the injury.